Analisis Korelasi antara Tingkat Pengetahuan mengenai Diabetes Melitus dengan Pola Gaya Hidup Pasien Diabetes Melitus Tipe 2 di Salah Satu Klinik Utama di Kota Bandung - Lestari, Regita Ayu (Prodi Farmasi - Universitas Al Ghifari, 2025)
Diabetes Mellitus (DM) is a chronic disease caused by impaired insulin production or reduced insulin effectiveness. Globally, the prevalence of type 2 DM continues to rise and is commonly associated with unhealthy lifestyle patterns. The management of type 2 DM not only relies on pharmacological therapy but also requires non-pharmacological interventions through lifestyle modifications. Adequate knowledge of the disease plays an important role in helping patients manage their daily lifestyle to reduce the risk of long-term complications and improve their quality of life. This study aims to analyze the relationship between the level of knowledge about diabetes mellitus and the lifestyle patterns of type 2 DM patients at a primary clinic in Bandung City. This research employed a quantitative method with a descriptive correlational design and a cross-sectional approach. Data were analyzed using the Spearman Rank Correlation test. The results showed a significant relationship between patients' knowledge levels and their lifestyle patterns (p = 0.000) with a correlation coefficient of 0.757, indicating a strong and positive relationship. Thus, the higher the patient’s knowledge about DM, the better the lifestyle they adopt. Keywords: Type 2 Diabetes Mellitus, knowledge, lifestyle, correlation, Spearman.